Climate change and migratory patterns of Fulani Herdsmen in Nigeria - Oluwakemi D. Udoh; Oluwayemisi E. Aforijiku; Ugochukwu D. Abasilim; Goddy Uwa Osimen (International Journal of Climate Change Strategies and Management, 2025)
Purpose – Climate change has emerged as a significant global challenge with far-reaching parallel implications, especially in regions where resource scarcity has led to various conflicts and displacement of people. This research aims to investigate the specific dynamics of Fulani Herdsmen’s migratory patterns as well as the socio-economic and security implications of such migration. Design/methodology/approach – This study relied on secondary data from published and unpublished sources. A qualitative research design was adopted and data was collected from scholarly works such as journals and reports published by various governmental organisations and NGOs. Findings – In Nigeria, the intersection of climate change and resource competition has notably affected the Fulani Herdsmen, a predominantly nomadic pastoralist group. The changing climate, marked by erratic rainfall, prolonged droughts and desertification, has disrupted traditional migration routes, compelling the Fulani Herdsmen who are constantly in search of grazing lands to migrate thereby, often leading to conflicts with sedentary populations. Originality/value – While previous studies have explored the relationship between climate change, resource scarcity and conflict, this research seeks to investigate the specific dynamics of Fulani Herdsmen’s migratory patterns and the socio-economic and security implications of such migration. Using the eco-violence theory of Homer-Dixon and the push-pull migration theory of Lee as the theoretical framework, this study analyses how climate change-induced migration has exacerbated tensions between herdsmen and host communities. The research emphasises the need for effective legal and policy frameworks to mitigate these conflicts, proposing sustainable strategies for promoting peaceful coexistence and resilience among affected populations.